Hermaphrodite life history and the maintenance of partial selfing in experimental populations of Caenorhabditis elegans - Carvalho, Sara (2015)
Classic population genetics theory predicts that mixed reproductive systems, where self reproduction (selfing) and outcrossing co-exist, should not be as common as they are in nature. One means of reconciling theory with observations is to recognize that sexual conflict between males and hermaphrodites and/or constraints in the allocation of resources towards sex functions in hermaphrodites can balance the fitness components of selfing and outcrossing.